Experiences of medical teachers in flipped learning for medical students: a phenomenological study - Park, Kyung Hye; Park, Kwi Hwa; Chae, Su Jin (Korean journal of medical education, 2018)
The purpose of this study was to explore the experience of medical teachers in the process of adapting flipped learning method through a phenomenological approach. Semi-structured interviews with five medical teachers from two medical colleges and one medical school were conducted in December, 2017. Data analysis was done according to Colaizzi's descriptive phenomenological methodology. A total of 160 unique significant statements were extracted. These statements generated 17 formulated meanings that were categorized into seven theme clusters and four theme categories. Main themes were: (1) teacher with high levels of passion and motivation; (2) hurdles of flipped learning: students were still passive, struggling in preparing for flipped learning; (3) positive changes from flipped learning: changes to classroom environment and teachers' reflection through experience; and (4) challenges of flipped learning: remaining tasks for teachers, expansion of flipped learning. Through phenomenological approach, researchers were able to elucidate categories about the experience of medical teachers when attempting flipped learning. Although medical teachers did not have the exact same idea on how flipped learning was conducted and implemented, the perception of flipped learning, or difficulties in class activities, they were still wondering how they could teach students well. This study might draw more attention to flipped learning and stimulate educational and institutional supports to improve teaching and learning in medical schools.